Integracja europejska a zróżnicowanie rynków kapitałowych - Koralun-Bereźnicka, Julia (European Integration and the Capital Markets Diversity, 2008)
The progress of European economic integration is a process which undeniably also affects capital markets. As a result, a gradual growth of convergence level between European stock exchanges can be expected, which is the hypothesis of the research. The aim of the paper is to examine the effects of capital markets integration in Europe by measuring the differentiation level of selected stock exchanges within this area. It is verified with the use of a synthetic stock markets integration index. The diversity is evaluated on the basis of 48 monthly variables from the period of 2003-2006, taken from Federation of European Securities Exchange. The variables were categorized into three groups: capital market size, equity, and bonds market. The conclusion drawn from application of the aggregated index of stock markets integration is the convergence level increase between European capital markets in the analysis period, which supports the initial hypothesis. The most significant harmonization growth refers to equity markets. A less intensive diversity decrease can also be observed in case of bond markets. However, the analysis does not reveal integration growth in the area of stock markets size.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 305-313